Influence of risky and protective behaviors connected with listening to music on hearing loss and the noise induced threshold shift among students of the Medical University of Bialystok - Modzelewska, Beata; Samluk, Anna; Wałejko, Łukasz; Muszyński, Paweł; Szczepańska, Joanna; Kleszczewska, Ewa (Family Medicine & Primary Care Review, 2017)
Background . Currently, significant changes have occurred in the character of sound exposure, along with the properties of the group affected by it. Thus, primary care physicians have to keep in mind that a sizable group of young adults comprises groups in which the prevalence of hearing loss is increasing. Objectives . The goal of the following study was to determine the auditory ability of the students attending the Medical University in Bialystok and to analyze their risky and protective behaviors relating to music consumption. Material and methods . In total, 230 students (age: 18–26 years) completed a questionnaire about general personal information and their music-listening habits. Thereafter, pure tone audiometry at standard frequencies (0.25 kHz–8 kHz) was performed. Results . Hearing loss was more frequent in subjects who listened to music at higher volumes (‘very loud’ – 22.2%, ‘loud’ – 3.9%, ‘not very loud’ – 2.1%, ‘quiet’ – 9.1%, p = 0.046). Hearing loss was more prevalent among those students who were living in a city with more than 50,000 inhabitants before starting higher education compared to the remaining subjects (7.95% vs. 0.97%, p = 0.025). Conclusions . The study demonstrated that surprisingly few medical students suffer from hearing loss or a noise induced threshold shift. There is no correlation between risky behavior such as a lengthy daily duration of listening to music or the type of headphone used and hearing loss. Hearing screening tests connected with education are indicated in the group of young adults due to the accumulative character of hearing damage.